Potential carcinogenic effects of world trade center dust after intratracheal instillation to Sprague–Dawley rats: First observation1. Issue 2 (19th September 2012) - Soffritti, M.; Falcioni, L.; Bua, L.; Tibaldi, E.; Manservigi, M.; Belpoggi, F.
Abstract Background More than 10 years have passed since the terrorist attack on the New York City World Trade Center on September 11, 2001. It is well known that long‐term carcinogenic bioassays on rodents can predict the potential carcinogenic effects of chemical and physical agents for humans. Objective A life‐span carcinogenicity bioassay was conducted on Sprague–Dawley rats at the CMCRC of the Ramazzini Institute to test the potential carcinogenic effects of settled dust collected at the WTC immediately after the terrorist attack. Methods The WTC material tested is a complex mixture of coarse particles (95%) contain pulverized cement, glass fibres, asbestos, lead, polycyclic aromatic hydrocarbons (PAHS), polychlorinated biphenyls (PCBS) and polychlorinated furans, and dioxin. The test matter was suspended in sterile saline and administered by intratracheal instillation (IT) to 8‐week‐old Sprague–Dawley rats (100 animals/sex), 3–4 days/week for 4 weeks. A group of 200 male and female rats served as controls. The animals were kept under observation until natural death. Results Histopathological evaluation of the lungs (target organ) of instilled control and treated male and female rats, did not show any significant increased incidence of lung tumors. Two hemangiomas (one with endothelial atypia) and one hemangiosarcoma were found in the lungs of treated males. Moreover a modest increased incidence of terminal bronchiolar hyperplasia (TBH) and squamous metaplasia occurred in the lung of treated males and females compared to the controls. Conclusion Hemangioma and hemangiosarcoma are extremely rare tumors in the lung of our colony and we believe they are caused by WTC dust. Am. J. Ind. Med. 56:155–162, 2013. © 2011 Wiley Periodicals, Inc.